OS12.4 In vivo dynamics and targeting of vessel co-option in glioma. (6th September 2019) - Seano, G; Griveau, A; Shelton, S; Krishnan, S; Wang, N; Kloepper, J; Huillard, E; Batchelor, T; Stemmer-Rachamimov, A; Aghi, M; Jain, R; Rowitch, D
Abstract: BACKGROUND: Gliomas comprise heterogeneous malignant glial and stromal cells. While blood vessel co-option is a potential mechanism to escape anti-angiogenic therapy, the relevance of glial phenotype in this process is unclear. MATERIAL AND METHODS: Here, we intravitally study preclinical syngenetic models of glioma as well as patient-derived cells transplanted orthotopically. Moreover, we profoundly confirm our preclinical results with histological studies on patient specimens. RESULTS: We show that Olig2+ oligodendrocyte precursor-like glioma cells invade by single-cell vessel co-option and preserve the blood-brain barrier (BBB). Conversely, Olig2-negative glioma cells form dense perivascular collections and promote angiogenesis and BBB breakdown, leading to innate immune cell activation. Experimentally, Olig2 promotes Wnt7b expression, a finding that correlates in human glioma profiling. Targeted Wnt7a/7b deletion or pharmacologic Wnt inhibition blocks Olig2+ glioma single-cell vessel co-option and enhances responses to temozolomide. Finally, Olig2 and Wnt7 become upregulated after anti-VEGF treatment in preclinical models and patients. CONCLUSION: Here, we show that glioma is able to employ vessel co-option, i.e. the movement of tumor cells towards and along the pre-existing vasculature. Glioma oligodendrocyte-like (OPCL) cells express Wnt7 that is necessary for vessel co-option and Wnt inhibitors significantly improve survival with temozolomide. Moreover, we demonstrated that anti-VEGF-treatment of glioma selects for Olig2/Wnt7+ cells